Efficacy and safety of co-administered ivermectin plus albendazole for treating soil-transmitted helminths: A systematic review, meta-analysis and individual patient data analysis. - Marta S Palmeirim; Eveline Hürlimann; Stefanie Knopp; Benjamin Speich; Vicente Belizario; Serene A Joseph; Michel Vaillant; Piero Olliaro; Jennifer Keiser (Public Library of Science (PLoS), 2018)
The soil-transmitted helminths (STH), Ascaris lumbricoides, Trichuris trichiura and hookworms, infect 1.5 billion people worldwide and cause an estimated burden of 3.3 million disability-adjusted life years (DALYs). Current control strategies focus on morbidity reduction through preventive chemotherapy (PC) but the most commonly used recommended drugs (albendazole and mebendazole) are particularly inefficacious against T. trichiura. This, together with the threat of emerging drug resistance, calls for new control strategies, including co-administration with other anthelminthics. Ivermectin plus albendazole is widely used against lymphatic filariasis, but its efficacy and safety against STH infections has not yet been fully understood.We conducted a systematic literature review and meta-analysis on the efficacy and safety of ivermectin-albendazole co-administration in five different databases (i.e. PubMed, ISI Web of Science, ScienceDirect, CENTRAL and clinicaltrials.gov) from 1960 to January 2018. Four studies reporting efficacy of ivermectin-albendazole against STH infections and five studies on its safety met the selection criteria and were included for quantitative analysis. Ivermectin-albendazole was significantly associated with lower risk (risk ratio (RR) = 0.44, 95% confidence interval (CI) = 0.31-0.62) for T. trichiura infection after treatment compared to albendazole alone. The co-administration revealed no or only a marginal benefit on cure and egg reduction rates over albendazole alone for A. lumbricoides and hookworm infections. Adverse events (AEs) occurring after ivermectin-albendazole co-administration were mostly mild and transient. Overall, the number of individuals reporting any AE was not different (RR = 1.09, 95% CI = 0.87-1.36) in co-treated and albendazole-treated patients. However, although not statistically significant, sub-group analysis showed a tendency for slightly more AEs in patients with filariasis treated with ivermectin-albendazole compared to those treated with albendazole alone (RR = 1.29, 95% CI = 0.81-2.05).Our findings suggest a good tolerability and higher efficacy of ivermectin-albendazole against T. trichiura compared to the current standard single-dose albendazole treatment, which supports the use of this co-administration in PC programs. Large-scale definitive randomized controlled trials are required to confirm our results.